Biochemical Markers and Public Health Measures in the Prevention and Management of Postoperative Complications in Pediatric Surgery - Arshad Kamal, Nazia Jameel, Ramsha, Amjad Azam Baloch, Suresh Kumar, M. Shakil Zari Khawri Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative complications in pediatric surgery contribute significantly to morbidity, prolonged hospitalization, and increased healthcare burden, particularly in resource-limited settings. Early biochemical indicators combined with preventive public health measures may improve clinical outcomes. This study assessed the predictive value of biochemical markers and the impact of public health interventions on postoperative complications among pediatric surgical patients. Methods: A prospective multicenter study was conducted at the Department of Pediatric Surgery, Lady Reading Hospital Peshawar, and the Sindh Institute of Child Health and Neonatology Sukkur from January 2022 to March 2023. A total of 100 pediatric patients aged 1 month to 12 years undergoing elective or emergency surgery were enrolled. Biochemical markers including C-reactive protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6), and serum lactate were measured preoperatively and on postoperative Days 1, 3, and 5. Public health interventions were implemented simultaneously, consisting of enhanced infection-control measures, parental education, vaccination verification, environmental sanitation audits, and antibiotic stewardship practices. Postoperative complications and clinical outcomes were monitored and analyzed. Results: Children who developed postoperative complications demonstrated significantly elevated levels of CRP, PCT, IL-6, and serum lactate at all postoperative time points. These biomarkers showed strong predictive value for surgical site infections, sepsis, and delayed wound healing. Public health measures substantially reduced postoperative morbidity, with decreases in surgical site infections, sepsis, delayed healing, and readmission rates. Relative reductions ranged from 30% to 45%, reflecting the effectiveness of combining preventive strategies with laboratory monitoring. Conclusion: Biochemical markers serve as reliable predictors of postoperative complications in pediatric surgery. When integrated with structured public health interventions, they result in marked reductions in morbidity and improved postoperative recovery. This combined approach offers a practical and effective model for strengthening pediatric surgical outcomes in resource-limited healthcare environments. Keywords: Pediatric surgery; postoperative complications; biochemical markers; CRP; procalcitonin; IL-6; serum lactate; public health measures; infection control; sepsis.